PROSPECT ON DIAPAUSE OF THE ORIENTAL FRUIT MOTH IN THE DORMENT PERIOD OF THE PEACH TREE - POLTRONIERI, Alex Sandro; MONTEIRO, Lino Bittencourt; SCHUBER, Joselia Maria (Scientia Agraria, 2008)
In order to observe the diapause of the oriental fruit moth during the dormant period of peach trees, G. molesta adults and caterpillars were monitored in four ‘Chimarrita’ peach orchards, between April and August 2006, in Araucária, PR, Brazil. Adults were monitored with two Delta traps per orchard; in addition, two traps were installed in a forest patch near one of the orchards, located 100 m away from the peach trees, to observe the occurrence of moth catches out of the orchard. Caterpillars were monitored with strip traps installed in thirty plants per orchard, and in plants that could serve as alternative hosts for the insect; also, the recesses on the trunks and primary branches were inspected visually. The Delta traps revealed the occurrence of oriental fruit moth adults in the orchards during the peach dormancy period; however, no captures occurred in traps placed in the forest. No G. molesta caterpillars were found in the strip traps or in the visual analyses of peach trees and plants that could serve as alternative hosts.